Dario Argento's world of horror - Argento, Dario; Soavi, Michele, 1957-; Farmer, Mimsy, 1945-; Malden, Karl; Pleasence, Donald; Savini, Tom; Lattanzi, Claudio; Connelly, Jennifer (Synapse Films, 1998)
"World of Horror is an incredible visual essay on the films of Dario Argento. Highlighting the early films of his career and containing interviews, amazing behind-the-scenes footage and clips from such films as Deep Red, Phenomena, Tenebrae and Demons ..."--Container.